2011
DOI: 10.3402/tellusa.v63i1.15772
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of climate change impact on water resources in the Pungwe river basin

Abstract: A B S T R A C T The Rossby Centre Regional Climate Model (RCA3) and the hydrological model HBV were linked to assess climate change impacts on water resources in the Pungwe basin until 2050. RCA3 was capable of simulating the most important aspects of the climate for a control period at the regional scale. At the subbasin scale, additional scaling was needed. Three climate change experiments using ECHAM4-A2, B2 and CCSM3-B2 as input to RCA3 were carried out. According to the simulations annual rainfall in 2050… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…They then discussed the implications of the effects of the climate change projections and identified relevant adaptation strategies and their limitations and facilitating factors (Andersson et al 2009;Andersson et al 2010). The empirical material used in this paper is mainly based on the results of interviews undertaken in the PAMO project supplemented by material from the project's participatory workshops.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…They then discussed the implications of the effects of the climate change projections and identified relevant adaptation strategies and their limitations and facilitating factors (Andersson et al 2009;Andersson et al 2010). The empirical material used in this paper is mainly based on the results of interviews undertaken in the PAMO project supplemented by material from the project's participatory workshops.…”
Section: Methodsmentioning
confidence: 99%
“…While climate scenarios show a drying in the western region of South Africa (Schulze 2011), regionally downscaled climate change projections for the study area, indicated wetter conditions with higher average annual and summer rainfall and fewer days with low river flow. In addition, the frequency of dry and wet extremes could increase (Andersson et al 2009;Graham et al 2011).…”
Section: The Study Area and The Two Farming Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there have been some studies on climate change within this region there are none specific to the Kwanza River Basin, in Angola. Some of the most recent studies in southern Africa region assessed the Zambezi River Basin [10], the Okavango delta in Botswana [11][12][13][14] and the Pungwe River Basin in Zimbabwe and Mozambique [15].…”
Section: Introductionmentioning
confidence: 99%